Eksistensi Multi-Party Interim Appeal Arbitration Arrangement Sebagai Arbitrase Pasca Kekosongan Anggota Appellate Body World Trade Organization - Rani Sri Wahyuni; Zulfikar Jayakusuma; Ledy Diana (Pattimura Legal Journal)
Introduction: The World Trade Organization (WTO), as a World Trade Organisation, has a dispute settlement system that allows member countries to comply with the results of the dispute decision through several stages of settlement, namely consultations, panels and the Appellate Body. Since 2017, one of the WTO's member countries, the United States, has not agreed to the appointment of Appellate Body members, resulting in a vacancy in the Appellate Body and its inability to resolve appeals since 2019. To provide a temporary solution to the Appellate Body's dysfunction, several WTO members have established an alternative dispute settlement body, the Multi-Party Interim Appeal Arbitration Arrangement. The establishment of this body is intended to fill the temporary void created by the Appellate Body's dysfunction.